PRESENTASI DIRI MAHASISWI SEBAGAI ISTRI SIRI DI KOTA PEKANBARU - Harianti, Ririn Indah; Salam, Noor Efni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
God created a man living in pairs as husband and wife, to build a household bound in a sacred promise of Kabul marriage (marriage contract). If the marriage contract has been established, then they have promised and will be faithful to build a house that is a preadulteress and Mawadah Warohmah. Marriage is not only a condition that must be exercised in religion, but also as a legitimate place of sex distribution. The Islamic religion has set the only way to meet human biological needs with only marriage. According to law number 1 year 1974 about marriage can be concluded that, a legitimate marriage is a marriage that occurs when obtaining a status of clear both legally and religiously. The method used in this study is a qualitative method with a phenomenological approach. The location of this research was conducted in Pekanbaru, as for the subject in this study as an informant that is a coed who has status as the wife of Siri namely YS, MR, ES, and AK. The data collection techniques in this study use observations, in-depth interviews and documentation. Data analysis techniques refer to the interactive models of Huberman and Miles which state the existence of interactive properties between collective data or data collection with data. analysis. The validity of data participation, triangulation and data adequacy techniques Based on the research that the author has done about the self-presentation of a coed as a wife series in Kota Pekanbaru, it can be concluded as follows: The front stage tells of the life of the informant when it does not have a status As the wife of Siri. At the time of the student has not status as a wife series they look like a typical coed in general who use hijab and Shar'i clothing because of the demands of the campus. Physically, the informant has a thin physique and a less attractive appearance because only makeup is only and not very fashionable, they are active in various campus activities in the field of arts, spiritual and lecture to Hides its original identity. At the time of the student has a status as the wife of Siri is in the back, they look sexy and beautiful because of the demands of the husband. In addition to demands, differences in appearance and style can be seen where they look more fashionable, using makeup that is rather excess than usual and more flirty. This distinction can also be seen from their activities of the diampus that sometimes have problems several times repeating courses. The reason they want to be the wife of Siri is due to meet the needs of life and sexual, avoid adultery and help families who do not have children to get children, and the trauma of a previous marriage.Key words : Self Presentation, Siri Wife